Democratic decision-making : historical and contemporary perspectives - Schaefer, David Lewis, 1943- (Lexington Books, 2012)
Democratic Decision-Making: Historical and Contemporary Perspectives contains eight essays by political scientists, all but one of them previously unpublished, addressing various aspects of the democratic decision-making process.